Role of Fe dynamic in release of metals at Rio Doce estuary: Unfolding of a mining disaster. (May 2021) - Queiroz, Hermano M.; Ying, Samantha C.; Bernardino, Angelo F.; Barcellos, Diego; Nóbrega, Gabriel N.; Otero, Xosé L.; Ferreira, Tiago O.
Abstract: The role of Fe oxyhydroxides dynamic on metal bioavailability was studied in the Rio Doce estuary after the largest mining disaster in the world. Soon after the disaster in 2015, metals were associated with Fe oxyhydroxides under a redox-active estuarine environment. Our results indicate that organic matter inputs from plant colonization on deposited tailings over estuarine soils led to a reductive dissolution of Fe oxyhydroxides within two years. Soil pseudo-total Fe content decreased by 70% between 2015 and 2017, while the total metal contents (Cr, Cu, Ni, Pb, and Zn) decreased by 79% in the soil. The losses of Fe and metals coupled to changes in Fe oxides crystallinity reveal a future ephemeral control of Fe oxyhydroxides over metal immobilization. Our results suggest a potential chronic contamination at the estuary and points to an aggravating scenario for the following years due to the increasing dominance of poorly crystalline Fe oxyhydroxides. Highlights: Massive Fe and metal losses took place within two years after the Samarco disaster. Inputs of organic matter increase the dissolution of Fe oxides within mine tailings. Loss in the crystallinity of Fe oxides weakens the soil capacity to immobilize metals. A chronic contamination is expected at Rio Doce estuary for the following years.